Antiphospholipid syndrome in obstetrics. (October 2018) - Kemp, M; Thomas, W
Antiphospholipid syndrome (APS) covers a spectrum of clinical manifestations ranging from recurrent pregnancy loss and obstetric complications from placental dysfunction through to thrombotic disease. This article will focus on the common manifestations of the pregnancy-related complications of APS. This includes clinical manifestations, diagnosis and management, as general practitioners will need to be able to recognize the disorder and will also have patients under their care receiving treatment for APS.